Genome-Wide Analysis of the Soybean TIFY Family and Identification of GmTIFY10e and GmTIFY10g Response to Salt Stress - Liu, Ya-Li; Zheng, Lei; Jin, Long-Guo; Liu, Yuan-Xia; Kong, Ya-Nan; Wang, Yi-Xuan; Yu, Tai-Fei; Chen, Jun; Zhou, Yong-Bin; Chen, Ming; Wang, Feng-Zhi; Ma, You-Zhi; et al. (Frontiers in Plant Science, 2022)
TIFY proteins play an important role in plant abiotic and biotic stress responses. Our transcriptome data revealed several TIFY family genes with significantly upregulated expression under drought, salt and ABA treatment. Few studies assessed TIFY family genes and how they affect salt stress tolerance in soybean. We identified 38 GmTIFY genes and analyzed their phylogenetic relationship, sequence structures, molecular weights and isoelectric points. The gene duplication and selective pressure analysis found that more duplication events and positive selection pressure occurred in TIFY3 and TIFY10 homology genes. The expression profile analysis found that TIFY10 and TIFY11 homology genes had significantly response to drought, salt and ABA treatment. Six significantly upregulated GmTIFY genes were selected to verify by RT-qPCR and the results demonstrated that GmTIFY10e and GmTIFY10g were more significantly response to salt stress. Overexpression of GmTIFY10e and GmTIFY10g in Arabidopsis and soybean could improve the salt tolerance of plants, while the RNAi of these two genes significantly increased sensitivity to salt stress in soybean. Further analysis demonstrated that overexpression of these two genes could improve the expression level of genes related to the ABA signal pathway. This study provides a basis for the future comprehensive analysis of soybean TIFY genes in stress response.